Status of Agri-tourism in Punjab - Samjetsabam Pinky and Dr. R.K. Dhaliwal, (Indian Journal of Extension Education, 2017)
The present paper analyses the status of agri-tourism in Punjab state, India. The study was undertaken by randomlyselecting 15 registered farmers from Punjab Heritage and Tourism Promotion Board. The data was collected by selfinterviewing the respondents and through mailed questionnaire. Findings of the study showed that 40 per cent ofthe respondents were gold membership holder followed by diamond and silver. The daily visit as well as theovernight charge varies for each agri-tourism unit. The least charge was of Jyani natural farm near district Ferozpur.During kharif and rabi season the main crop grown were rice and wheat, respectively, while under plantation cropskinnow had the maximum area and all the agri-tourism units had complete source of irrigation facilities. More thanhalf of the respondents were having large size farm house. Virasat Haveli near Amritsar had the maximum number oftourists annually as it was easily accessible by the tourists whereas the Chandigarh Sardar farm near FatehgarhSahid had the lowest number of tourists. All the agri-tourism units offered recreational activities followed byproductional and processing activities.